Feminist Approaches In Islamic Studies - Kholidatun Nur Wahidiyah; Zulfi Mubaraq; Syuhadak Syuhadak; Raden Taufiqurrochman (Medina-te : Jurnal Studi Islam, 2023)
The purpose of this writing is to understand 3 things: first, the concrete form of the feminist approach. Second, the factors that influence the existence of a feminist approach in Islamic studies. Third, the implications of academic feminist approaches to the dynamics of Islamic studies. The author uses the literature method by using a feminist approach in studying Islam. The results of this study show that first, feminist etymology comes from the word femme (single woman) who fought to fight for the rights of women as a social class. In terminology a women's movement that demands full equality. Second, internal factors include low knowledge and understanding of the community about religious values related to the role and function of women, the reality of Muslim society that still experiences gender bias, as well as the essence of women's bodies.external factors include the number of religious interpreters who harm the position and role of women as well as patriarchal culture that has long dominated in society (political, economic, and biased interpretation of religious texts gender). Third, positive impact: The existence of the term career woman makes women become more independent women, women are not oppressed by the capitalist system, and are productive in doing things outside the domstic. Negative impact: Negative impact (the birth of various lesbian feminism movements or the practice of free sex between women and women), and There are several ideologies of the feminism movement that are not in accordance with Islamic corridors